CLRM-09 FIRST-LINE Tumor TREATING FIELDS (200 KHZ) THERAPY FOR NEWLY-DIAGNOSED GLIOBLASTOMA: THE PHASE 3 TRIDENT TRIAL (EF-32). (5th August 2022) - Shi, Wenyin; Kleinberg, Lawrence; Jeyapalan, Suriya A; Goldlust, Samuel A; Nagpal, Seema; Roberge, David; Nishikawa, Ryo; Grossman, Rachel; Glas, Martin
Abstract: BACKGROUND: Tumor Treating Fields therapy (TTFields; 200 kHz) comprise alternating electric fields that disrupt cancer cell division, and is approved for newly diagnosed glioblastoma (ndGBM), recurrent GBM and mesothelioma. In the phase 3 EF-14 trial, TTFields/temozolomide (TMZ) significantly increased overall survival (OS) and progression-free survival (PFS) vs TMZ alone in patients with ndGBM. TTFields-related adverse events (AEs) were mainly dermatological with no increases in systemic toxicity. In preclinical models, the addition of TTFields to radiotherapy (RT) increased the therapeutic effect. Additionally, TTFields added to RT/TMZ was reported as feasible and well-tolerated in 2 clinical pilot phase 2 studies. MATERIALS AND METHODS: TRIDENT (EF-32; NCT04471844) is an international, phase 3 randomized trial comparing TTFields (200 KHz, ≥18 h/day)/RT/TMZ vs RT/TMZ alone. Adult patients (N=950; ≥18 years of age [≥22 years of age; US]) with histologically confirmed ndGBM, Karnofsky Performance Status ≥70, life expectancy ≥3 months, adequate organ function and eligible for RT/TMZ will be enrolled. Patients will be stratified by extent-of-resection and MGMT promoter methylation status and randomized 1:1 to receive continuous TTFields/RT/TMZ or RT/TMZ during the investigational period. Subsequently, all patients will receive TTFields/6 cycles of maintenance TTFields/TMZ; TTFields will continue for 24 months or until second disease progression per Response Assessment in Neuro-Oncology (RANO). The primary endpoint is median OS. Secondary endpoints include median PFS (RANO), 1- and 2-year survival rates, overall radiological response (RANO), PFS6, PFS12, severity and frequency of AEs and quality-of-life, OS per TTFields duration-of-usage. The study is powered at 80% to detect a hazard ratio of <0.8 (5% type I error). The study is currently open to enrolment in Austria, Belgium, Czech Republic, France, Germany, Israel, Switzerland, and across the US.